1999
DOI: 10.1183/09031936.99.14613519
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and asthma and allergy in schoolchildren from Western Australia

Abstract: The association of environmental factors with atopic disease in children remains poorly understood. The aim of this study was to investigate the relationship between socio-environmental factors and symptoms of asthma and atopy in 6-7-yr-old children assessed as an adjunct to Phase I of the International Study of Asthma and Allergy in Childhood in Perth, Western Australia. Parental questionnaire responses were obtained for 2,193 children (73.6%) in 34 randomly selected primary schools in the Perth metropolitan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Comparative or secular studies are warranted in future investigations. Younger subjects and boys had a higher rate of physician-diagnosed asthma, which was consistent with other studies, 8,9,12,14,21,34,35 and the level of parental education and number of siblings were associated with the occurrence of childhood asthma. Parents with a higher education level and fewer children were more anxious about the specific health condition of their children; therefore, these children would be more likely to receive a diagnosis of asthma.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Comparative or secular studies are warranted in future investigations. Younger subjects and boys had a higher rate of physician-diagnosed asthma, which was consistent with other studies, 8,9,12,14,21,34,35 and the level of parental education and number of siblings were associated with the occurrence of childhood asthma. Parents with a higher education level and fewer children were more anxious about the specific health condition of their children; therefore, these children would be more likely to receive a diagnosis of asthma.…”
Section: Discussionsupporting
confidence: 81%
“…7 This does, however, suggest a role for environmental exposures in the cause of this evolving epidemic. 8 Many factors have been proved to be associated with the prevalence and/or attacks of asthma, including personal factors (smoking habits, genetics, age, sex, nutritional status, number of siblings, coexisting lung disease, lifestyle, allergy status, family history, and occupation) and environmental stimuli (house dust, animal danders, molds, cockroach infestation, occupational exposure, environmental tobacco smoke, indoor/outdoor air pollution, cooking fumes, aeroallergens, and climate). 9 -29 Both genetic and environmental factors are believed to contribute to the relationship.…”
mentioning
confidence: 99%
“…Prior studies have been inconsistent about whether carpets are risk factors for adverse health. For instance, studies have shown carpets to be associated with increased risk of asthma (Mohamed, Ng'ang'a et al 1995;Jaakkola, Ieromnimon et al 2006); decreased risk of asthma (Zock, Jarvis et al 2002), respiratory symptoms (Skorge, Eagan et al 2005;Trevillian, Ponsonby et al 2005), and eczema (Palmer, Valinsky et al 1999); or no effects on asthma (Voute, Zock et al 1994). The BASE study is not ideal for investigating risks associated with carpet, as 91 of 100 study spaces had carpet as a primary floor covering.…”
Section: Discussionmentioning
confidence: 99%
“…It is assessed that environmental factors plays a key role in their raise of occurrence. [7][8] The innumerable environmental factors include smoking habits, atopy, age, nutritional status, coexisting lung diseases, lifestyle, occupation, family size, and environmental stimuli that is, house dust, animal dander, mold spores and fragments, cockroach droppings, indoor/outdoor aeroallergens, pollution, climate. [9][10][11] Mathers and Loncar 2006 estimated that tobacco related deaths are expected to rise to 8.3 million in 2030.…”
Section: Discussionmentioning
confidence: 99%